2019
DOI: 10.3390/cancers11060754
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PD-1 and PD-L1 in Extramammary Paget Disease: Implications for Immune-Targeted Therapy

Abstract: Extramammary Paget disease (EMPD) is a locally aggressive cutaneous malignancy that usually arises in anogenital or axillary skin. Immune checkpoint inhibitors targeting programmed cell death receptor (PD-1) and/or its ligand (PD-L1) are approved for the treatment of several types of cancer, and response to these generally correlates with increased PD-L1 expression by tumor cells. The expression of PD-L1 and composition and density of the tumor-associated immune infiltrate in EMPD have been little studied. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…In addition, PD-L1 expression in ICs was significantly lower in patients with HER2-positive compared with HER2-negative EMPD cancers. 35 Duverger et al reported positive expression of PD-L1 on cancer cells in n = 4/7 invasive EMPD, 36 while Karpathiou et al reported that EMPD are characterized by the intense lymphocytic response but without PD-L1 expression on either cancer or immune cells. 37 A single patient in our cohort was included in a basket trial with Pembrolizumab without clinical benefit and a later tumor sample analysis revealed no PD-L1 positivity, but HER2 amplification was detected and Herceptin therapy was initiated (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PD-L1 expression in ICs was significantly lower in patients with HER2-positive compared with HER2-negative EMPD cancers. 35 Duverger et al reported positive expression of PD-L1 on cancer cells in n = 4/7 invasive EMPD, 36 while Karpathiou et al reported that EMPD are characterized by the intense lymphocytic response but without PD-L1 expression on either cancer or immune cells. 37 A single patient in our cohort was included in a basket trial with Pembrolizumab without clinical benefit and a later tumor sample analysis revealed no PD-L1 positivity, but HER2 amplification was detected and Herceptin therapy was initiated (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…infiltrate. 5 They found that PD-1 was expressed heavily by the tumor-associated immune infiltrate in all EMPD cases analyzed. Similar to the previously mentioned study, 6 PD-L1 was expressed by tumor cells in a few cases only.…”
Section: Pd-1 Expression In Empd: Implication For Immunotherapymentioning
confidence: 94%
“…Current data for targeted therapy have focused on HER2 (human epidermal growth factor receptor 2) hormone receptor expression, 18 ERBB (erythroblastic oncogene B) amplification, 19 CDK4 (cyclin-dependent kinase 4)-cyclin D1 signaling, 20 and most recently PD-1/PD-L1 pathway. [5][6][7]…”
Section: Resident Pearlsmentioning
confidence: 99%
See 2 more Smart Citations